Instrument development of attitudes towards egalitarian education scale - Nik Muhammad Hanis Nek Rakami; Mohd Muslim Md Zalli; Nik Ahmad Hisham Ismail; Noor Lide Abu Kassim; Jin Yulu (Journal of Education and Learning (EduLearn), 2026)
This paper discusses the instrumentation process that was developed to measure teachers’ attitudes towards egalitarian education in the context of a multiracial society. The researchers have developed a new, culturally relevant survey to assess a previously unexplored construct (teachers’ attitudes towards egalitarian education). Researchers have employed an eight-step process: i) operationalizing the meaning of attitudes towards egalitarian education; ii) identifying a theoretical framework on attitudes towards egalitarian education; iii) exploring dimensions of attitudes from focus group discussion; iv) drafting preliminary items on egalitarian education based on focus group findings; v) validating the content of the attitudes towards egalitarian education items via expert judgment; vi) conducting a pilot test of the attitudes towards egalitarian education scale; vii) finalizing the attitudes towards egalitarian education scale; and viii) translating the attitudes towards egalitarian education scale. This is the first validated instrument specifically developed for Malay teachers, addressing a critical gap in egalitarian educational research. The careful development process ensures that the questionnaire accurately measures the issues raised in the study. This study provides clear information on how the egalitarian education attitudes scale is implemented and establishes a foundation for future cross-cultural adaptations in similar educational settings.